ANALISIS TINGKAT KESEHATAN KOPERASI UNIT SIMPAN PINJAM KP-RI PRIMA HUSADA BANGKINANG TAHUN 2019-2021 - Alda Nur Arafah; Rahmawati Rahmawati; Helmiati Helmiati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study aims to determine the health level of the savings and loan unit cooperatives KP-RI prima husada bangkinang in 2019-2021 based on the regulation of the deputy for supervision of the ministry of cooperatives and small and medium enterprises of the republic of Indonesia number 06/Per/Dep.6 IV/2016 cocerning guidelines for assessing cooperative health, savings and loands and cooperative savings and loan units that involve aspect of capital, quality of productive data. In this study, data were collected throught file research and interview methods. The result showed that the health level of the savings and loan unit cooperative KP-RI prima husada bangkinang for three consecutive years (2029-2021) obtained total score of 71,85 in 2019, in 2020 it received a score of 70,65 and in 2021 it obtainted a score of 72,45. the average score can be categorized quite healthy.